Brain-related outcome measures in trials recruiting critically-ill children. Issue 6 (December 2019) - Fink, Ericka L.; Tasker, Robert C.
Abstract : Purpose of review: Randomized controlled trials leading to innovations that improve outcomes in acute life-threatening illnesses in children are scarce. A key issue is how we refocus research on outcomes that matter and are more relevant to those making emergency decisions, and those involved with managing and living with the late-outcome. We have used information from recent trials in critically ill children – in particular those illnesses without any primary neurologic involvement – to develop an approach to brain-related outcomes that will maximize child and family benefit from research. Recent findings: Fifteen recent pediatric critical care trials illustrate four types of brain-related outcomes assessment: death or organ-system-failures – as illustrated by studies in systemic illness; neurological and neuropsychological outcomes – as illustrated by the glycemic control studies; cognitive outcomes – as illustrated by a sedative trial; and composite outcomes – as illustrated by the therapeutic hypothermia studies. Summary: The 15 research trials point to five areas that will need to be addressed and incorporated into future trial design, including use of: neurologic monitoring during intensive care unit admission; postdischarge outcomes assessments; strategies to improve retention in long-term follow-up; child and family-centered outcomes; and core outcomes datasets.